Symposium on recent developments in data analysis - Hamill, J.; Van Emmerik, R.; Miller, R.; O'Connor, K.; Coffey, N.; Harrison, D. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The purpose of this symposium is to present recent developments in biomechanical data analyses in two areas. First, current methods used in a dynamical systems approach will be described. Second, two statistical approaches, Principal Components Analysis and Functional Data Analysis, will be presented. The emphasis in this symposium will be on how to use each of these recent analysis techniques.